2020
DOI: 10.1021/acsanm.0c00231
|View full text |Cite
|
Sign up to set email alerts
|

Modularly Constructed Polyhedral Oligomeric Silsesquioxane-Based Giant Molecules for Unconventional Nanostructure Fabrication

Abstract: Controlled assembly of nanoscale building blocks is a promising approach to obtain functional materials with unique properties. Here, we report a way to manipulate the supramolecular structures of giant molecules based on discotic triangle cores and isobutyl polyhedral oligomeric silsesquioxanes (BPOSS) nanoparticles (NPs). It is found that depending upon the number of BPOSS at the periphery of the discotic cores, the packing of these nanoscale components (discotic core and POSS) could be manipulated into eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Branched silsesquioxane units of [RSiO 1.5 ] n composition are among the most popular blocks for creating numerous hybrid nanomaterials and composites. Two general approaches in this chemistry are actively developing nowadays(i) the use of fully condensed silsesquioxanes generally based on octameric [RSiO 1,5 ] 8 cubane-like units and (ii) the application of partly condensed derivatives. Among many fascinating and functional structures, available via the first approach, we can mention polyhedral oligomeric silsesquioxanes (POSS) bearing chromophore groups, , materials for sorption of heavy-metal ions/dyes/organic solvents from water, additives for polymers, components of nanoscale building blocks, , shape amphiphiles, organocatalysts, building blocks for the construction of magnetic materials, and luminescent devices or light-harvesting systems. , …”
Section: Introductionmentioning
confidence: 99%
“…Branched silsesquioxane units of [RSiO 1.5 ] n composition are among the most popular blocks for creating numerous hybrid nanomaterials and composites. Two general approaches in this chemistry are actively developing nowadays(i) the use of fully condensed silsesquioxanes generally based on octameric [RSiO 1,5 ] 8 cubane-like units and (ii) the application of partly condensed derivatives. Among many fascinating and functional structures, available via the first approach, we can mention polyhedral oligomeric silsesquioxanes (POSS) bearing chromophore groups, , materials for sorption of heavy-metal ions/dyes/organic solvents from water, additives for polymers, components of nanoscale building blocks, , shape amphiphiles, organocatalysts, building blocks for the construction of magnetic materials, and luminescent devices or light-harvesting systems. , …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Often, the dodecagonal quasicrystal (DDQC) phase with 12-fold orientational symmetry and only one-dimensional (1D) translational symmetry are closely associated with F-K phases, due to similarities in local tetrahedral packing rules. [12][13][14] Complex F-K phases and the DDQC phase have not only been observed in broad soft matter systems, including diblock copolymers, [15][16][17][18][19][20][21][22][23] dendrimers, 13,[24][25][26][27][28][29][30][31] polymer colloids, 32 small molecular surfactants, [33][34][35] giant molecules, [36][37][38][39][40] and very recently, sugar-polyolefin conjugates, 41,42 but also mesoporous silica, 43,44 binary nanocrystal superlattices, 45,46 and DNA functionalized nanoparticles. 47,48 Several types of F-K phases only have considerably small differences between their overall free energies.…”
Section: Introductionmentioning
confidence: 99%
“…Using the giant shape amphiphiles developed by our group, we found that much less molecules will be required to form a spherical motif. 23,32,36,40,41 Therefore, the supramolecular assembly of giant shape amphiphiles could be a feasible pathway toward the unusual Z and C15 phases in single-component soft matter. Indeed, in our recent work, we discovered a series of unconventional spherical packing phases in giant shape amphiphiles, including the A15 phase, σ phase, dodecagonal quasicrystalline (DQC) phase, and body-centered cubic (BCC) phase, by functionalization of the perylene core with several polyhedral oligomeric silsesquioxane (POSS) cages.…”
Section: Introductionmentioning
confidence: 99%